Mechanization in African agriculture: A continental overview on patterns and dynamics - Oliver K. Kirui; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2018)
This study provides an overview on the patterns and dynamics of mechanization in African agriculture over the 10 year period (2005-2014). Farm level and value chain related mechanization are considered. This study looks in to pattern of agricultural mechanization along the entire value chain (production, post-harvest, processing, transport and storage) and compares it with the annual average agricultural output over the same time period. Clusters of countries are identified by grouping countries into those that have simultaneously experienced high growth rate in agricultural machinery and also in agricultural output, including; Angola, Botswana, Ethiopia, Malawi, Mali, Morocco, Niger, Rwanda, Tanzania, Togo, and Zambia. On the opposite side of the spectrum are countries with low growth in machinery and in agricultural output, and include for instance Madagascar, Zimbabwe, Uganda, and Egypt. In general, there is a positive correlation (of 0.52) between agricultural machinery growth and agricultural output growth in Africa, which is a classical two - way relationship, not to be interpreted as a causal one.
Keywords: Q01; Q18; D20; L64; 330; Agricultural mechanization; machinery; patterns; agri-food system; value chains; agricultural growth; Africa